Implementasi Pembelajaran Pendidikan Agama Islam dalam Membentuk Karakter Peserta Didik di Era Digital Revolusi Industri 4.0 di Kelas XII IPA 2 SMA N 1 Bayang Kabupaten Pesisir Selatan - Muhammad Alfahrisi; Sulaiman Sulaiman (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
Education is a very important aspect in creating quality human resources through quality learning. Therefore we need a way to realize quality education through effective and efficient learning in accordance with the times. The digital era of the Industrial Revolution 4.0 is now growing rapidly, because these technological developments cannot release humans to use technology in every activity of daily life. In this era, the world of education must be able to produce students who can keep up with technological developments that do not conflict with religious values. Guidance and coaching to students needs to be done in order to produce students who have the desired character. One solution to deal with these problems is to implement Islamic Religious Education learning that is oriented to shape the character of students in the digital era of the Industrial Revolution 4.0 in class XII IPA 2 SMA N 1 Bayang Pesisir Selatan Regency. The purpose of this study is to describe how the planning, implementation and evaluation of the implementation of Islamic Religious Education learning in the digital era of the Industrial Revolution 4.0 in class XII IPA 2 SMA N 1 Bayang Pesisir Selatan Regency. The findings in this study on the planning aspect, the school designed programs to shape the character of students. Furthermore, in the aspect of implementing learning in character building, it is carried out by utilizing digital media and applications. While the learning evaluation aspect uses three indicators, namely, effectiveness, adequacy and responsiveness. The results showed that the program implemented at the school consisted of intracurricular activities (Asma'ul Husna, profile of Pancasila learning (Propela), 3S refraction (Smile, Greetings, and Greetings), Dzuhur prayer in congregation, reading Asmaul Husna, habituation of disciplined life, habituation clean living, habituation of responsible attitude, Infaq every Friday) and extracurricular activities (Scouts, Islamic Intellectual Cadres, Paskibra, Arts, English Club, Volley Ball) that utilize digital media and applications in the learning process so as to be able to provide character changes to students. Students include the values of honesty, responsibility, discipline, independence and social care.